Application Of Design Patterns And Space Concepts In The Development Of Heat Pipes - Sharma, Korada Viswanatha (2010)

(untitled)
The phenomenon of condensation of vapors on a vertical fin is theoretically solved by coupling the thermal conduction in the fin to the constitutive equations of motion and energy of the condensate layer in an appropriate manner with relevant boundary conditions. The analysis accounts for the sub cooling effects of the condensate on the condensation heat transfer coefficient. A design equation that can be employed in the design of the condenser section of a flat plate heat pipe has been suggested in an earlier paper presented at the sixth international heat pipe conference held at Grenoble France. In an technical note published in the international journal of heat and mass transfer, the process of condensation on a vertical plate fin of variable thickness is analyzed to establish the effect of fin geometry on the condensation heat transfer coefficient. The results presented are of significance in the optimization of fin geometry while developing the flat plate heat pipes.In yet another paper published in the Canadian journal of chemical engineering explicit solutions are obtained for the problems of condensation of vapors on the lateral surface of a long vertical plate fin of variable cross section. The formulation yields solutions to the limiting cases so that the results can be employed in the design of the condenser section of a flat plate heat pipe in which the fin is considered to be an essential element for augmenting the condensation heat transfer.Design can be considered as an integral part along with the process know how and knowledge of fabrication/assembly of the ultimate product such as the radiation shield with embedded heat pipes as in the case of the present study within the frame workof agile manufacturing.